Antibacterial Efficacy of Turmeric (Curcuma domestica) Rhizome Infusion Against Aeromonas hydrophila and Its Toxicity - Azizah, Nur; Aji, Oktira Roka (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2023)
Aeromonas hydrophila bacteria can cause Motile Aeromonas Septicemia (MAS), a disease that impacts freshwater fish. The turmeric rhizome contains numerous bioactive compounds that act as antibacterials and might be utilized to inhibit A. hydrophila. This research aimed to identify the phytochemicals in turmeric (Curcuma domestica) infusion, evaluate its antibacterial activity against A. hydrophila, and define the toxicity effect of turmeric rhizome infusion. The agar dilution method was used to measure antibacterial activity, whereas the Brine Shrimp Lethality Test (BSLT) was used to assess toxicity. The research confirmed the presence of phytochemicals such as tannins, alkaloids, flavonoids, phenols, and saponins in a turmeric rhizome infusion. According to the findings, the infusion from turmeric rhizome effectively inhibited the growth of A. hydrophila at concentrations between 750-1000 ppm. In toxicity tests, the LC50 value of the turmeric rhizome infusion against shrimp larvae was 381.18 ppm. Hence, the turmeric rhizome infusion has the potential to be further developed for the prevention and treatment of fish infected with A. hydrophila in freshwater fish farming.